Muhammadiyah Education at Gempol Village during the Covid 19 Pandemic - Mukhammad Fahmi Udin; Muhlasin Amrullah (International Consortium of Education and Culture Research Studies, 2021)
The purpose of holding scientific articles is to train students' abilities to be more sensitive to the world of education in their surroundings, and also to complete assignments that have been given by lecturers to students. For the research method using descriptive qualitative methods or easier, namely using interviews, with this interview method, the information we need is easier to obtain and also obtained easily. Because the information we get comes directly from the source, so there is no misinformation in it. The results that I have obtained from the interviews and articles that I have made have had a significant impact on me regarding education in my own village and have also given me more insight into education. The conclusion that I can take is that in the implementation of teaching and learning activities it is not always done face to face but can be done online as it is today due to conditions that do not allow face to face learning, but still it is a maximum effort to connect the education chain without break the education chain.